2017
DOI: 10.1302/2046-3758.63.bjr-2016-0083
|View full text |Cite
|
Sign up to set email alerts
|

The effect of systemic administration of G-CSF on a full-thickness cartilage defect in a rabbit model MSC proliferation as presumed mechanism

Abstract: ObjectivesThe aim of this study was to investigate the effect of granulocyte-colony stimulating factor (G-CSF) on mesenchymal stem cell (MSC) proliferation in vitro and to determine whether pre-microfracture systemic administration of G-CSF (a bone marrow stimulant) could improve the quality of repaired tissue of a full-thickness cartilage defect in a rabbit model.MethodsMSCs from rabbits were cultured in a control medium and medium with G-CSF (low-dose: 4 μg, high-dose: 40 μg). At one, three, and five days af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…It was also demonstrated to increase MSCs at the microfracture sites of a full-thickness chondral defect and thereby enhance cartilage repair in vivo in New Zealand white rabbits (Truong et al, 2017). GM-CSF promotes repair of the damaged cartilage by stimulating proliferation of MSCs (Okano et al, 2014;Sasaki et al, 2017) whereas EGF binding to its receptor activates EGFR-mediated signaling which is crucial for the maintenance of chondrocyte number by protecting them from undergoing apoptosis during OA progression (Zhang et al, 2014;Jia et al, 2016). HGF was upregulated in OA cartilage and synovial fluids of patients compared to healthy subjects (Abed et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated to increase MSCs at the microfracture sites of a full-thickness chondral defect and thereby enhance cartilage repair in vivo in New Zealand white rabbits (Truong et al, 2017). GM-CSF promotes repair of the damaged cartilage by stimulating proliferation of MSCs (Okano et al, 2014;Sasaki et al, 2017) whereas EGF binding to its receptor activates EGFR-mediated signaling which is crucial for the maintenance of chondrocyte number by protecting them from undergoing apoptosis during OA progression (Zhang et al, 2014;Jia et al, 2016). HGF was upregulated in OA cartilage and synovial fluids of patients compared to healthy subjects (Abed et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This environment of cytokines may promote cell survival, migration, and differentiation. 8,32,36,45 Studies have shown that activation of FGF 43 and TGF-β 49 signaling pathways promote the repair of cartilage defects and the synthesis of extracellular matrix. This study confirmed the ability of the implanted hAMSCs to survive and differentiate into chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic growth factors recombinant polypeptides are: transforming growth factor beta (TGF-β1), bone morphogenetic protein (BMP)-2 and BMP-7 (also known as osteogenic protein-1, OP-1; each of the TGF-β superfamily); insulin-like growth factor-I (IGF-1); fibroblast growth factor-2 (FGF-2) and fibroblast growth factor-18 (FGF-18) of the fibroblast growth factor family and platelet-derived growth factor (PDGF) [80]. Several recent reports have indicated that the granulocyte-colony stimulating factor (G-CSF) serves not only as a growth factor for haematopoietic stem cells, but is also able to promote MSC mobilisation to both bone marrow and peripheral blood [81]. This discovery has been put into practice by Garay-Mendoza and colleagues, who conducted a prospective open-label, phase I/II clinical trial in patients with knee OA.…”
Section: Regenerative Medicine As a Novel Therapeutic Optionmentioning
confidence: 99%